Метод параметричних вимірювань з використанням генератора хаотичних коливань - Кучерук, В. Ю.; Маньковська, В. С. (Видавництво Національного університету «Львівська політехніка», 2009)
The method of measuring of parameters is considered on the basic chaotic generator. The attractor design in the Mathcad environment is conducted.
Keywords: the method of measuring; chaotic generator; Chua’s circuit; “strange attractor”; sencitivity; dynamical chaos